A comparative study of international standards for the development of the demolition guidelines for the Philippines - Galang, Gerald O.; Ramos, Virgilio E. Jr
The concept of urban development is incomplete without a full understanding of redevelopment. As such, demolition work is a vital practice in our developing country, the Philippines. Being hazardous in nature, it should have strict parameters that uphold high standards of safety fitting for the country's current conditions and practices. In the Philippines, there is an absence of well-documented techniques for demolition work. This research aims to benchmark the different international demolition codes, document the current situation of the demolition industry in the country, identify the demolition techniques commonly used, and to identify minimum elements to be included in a demolition guideline for the Philippines. A comparative map of the different codes was made and demolition contractors were surveyed in order to accomplish these objectives. These results were then integrated in order to form a discussion of possible elements that can be applied in the formation of demolition guidelines. The researchers suggested a structure containing the elements that suited local demolition practices.